Analysis of passing sequences, shots and goals in soccer - Hughes, M.; Franks, I. (Journal of Sports Sciences, 2005)
Early research into how goals were scored in association football (Reep and Benjamin, 1968) may have shaped the tactics of British football. Most coaches have been affected, to a greater or lesser extent, by the tactics referred to as the "long-ball game" or "direct play", which was a tactic employed as a consequence of this research. Data from these studies, published in the late 1960s, have been reconfirmed by analyses of different FIFA World Cup tournaments by several different research groups. In the present study, the number of passes that led to goals scored in two FIFA World Cup finals were analysed. The results conform to that of previous research, but when these data were normalized with respect to the frequency of the respective lengths of passing sequences, there were more goals scored from longer passing sequences than from shorter passing sequences. Teams produced significantly more shots per possession for these longer passing sequences, but the strike ratio of goals from shots is better for "direct play" than for "possession play". Finally, an analysis of the shooting data for successful and unsuccessful teams for different lengths of passing sequences in the 1990 FIFA World Cup finals indicated that, for successful teams, longer passing sequences produced more goals per possession than shorter passing sequences. For unsuccessful teams, neither tactic had a clear advantage. It was further concluded that the original work of Reep and Benjamin (1968), although a key landmark in football analysis, led only to a partial understanding of the phenomenon that was investigated.